2011
DOI: 10.1111/j.1365-3156.2011.02772.x
|View full text |Cite
|
Sign up to set email alerts
|

Health care‐seeking behaviour and diagnostic delays for Human African Trypanosomiasis in the Democratic Republic of the Congo

Abstract: Summary Objective  About half of the patients with Human African trypanosomiasis (HAT) reported in the Democratic Republic of the Congo (DRC) are currently detected by fixed health facilities and not by mobile teams. Given the recent policy to integrate HAT control into general health services, we studied health seeking behaviour in these spontaneously presenting patients. Methods  We took a random sample from all patients diagnosed with a first‐time HAT episode through passive case finding between 1 October 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 10 publications
0
40
0
Order By: Relevance
“…Previous studies of rHAT in Uganda have demonstrated that difficulties in accessing appropriate diagnostics can be a barrier to diagnosis [3335] and this is known to be a barrier throughout HAT endemic regions [24,36]. Further delays can be introduced by patients requiring a median of four visits to heath facilities and a seven months’ delay before being screened for gHAT [37]. Sensitisation of the public and health personnel was a core component of this new strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of rHAT in Uganda have demonstrated that difficulties in accessing appropriate diagnostics can be a barrier to diagnosis [3335] and this is known to be a barrier throughout HAT endemic regions [24,36]. Further delays can be introduced by patients requiring a median of four visits to heath facilities and a seven months’ delay before being screened for gHAT [37]. Sensitisation of the public and health personnel was a core component of this new strategy.…”
Section: Discussionmentioning
confidence: 99%
“…T. brucei is transmitted by the Glossina fly and proliferates extracellularly in blood and lymph, eliciting nonspecific influenza-like symptoms in the early stage of the disease. The advanced stage, which occurs months to years after infection, ensues from the parasite crossing the blood-brain barrier (BBB) and is characterized by severe neurological symptoms 4 . The World Health Organization (WHO) estimated that there were fewer than 3000 cases of T.b.…”
Section: Introductionmentioning
confidence: 99%
“…These include the requirement for a source of power and a cold-chain, and the 50 dose format of CATT means that when the reagent is reconstituted, the doses must be used within a few days in order to avoid spoilage [15,16]. To reduce this wastage, the Institute of Tropical Medicine (ITM) developed the CATT D10, which contains reagents for 10 tests [16,17]. Whilst the CATT D10 is thermostable, the vial of reagent must be used within 24 hours after opening, which has restricted its widespread use by national HAT control programmes.…”
Section: Introductionmentioning
confidence: 99%